Elimination method
System of linear equations can also be solved using the elimination method. We will show with examples.
Before you learn this lesson, make sure you understand how to solve
linear equations
Here are the steps to follow:
Step 1
Try to eliminate a variable as you add the left sides and the right sides of the two equations
Step 2
Set the sum resulting from adding the left sides equal to the sum resulting from adding the right sides
Step 3
Solve for the variable that was not cancelled or eliminated
Step 4
Use the answer found in step 3 to solve for the other variable by substituting this value in one of the two equations
Example #1: Solve the following system using the elimination method
x + y = 20
x − y = 10
Step 1
Examine the two equations carefully.Then, you will try to eliminate or cancel a variable by adding the left sides (x + y and x − y).
However, since you are adding the left sides, you have to the right sides (20 and 10) of the two equations also
For the equations above, it turns out that it is easy to eliminate y while adding the left sides since x + y + x − y = x + x + y − y = x + x + 0 = 2x
Step 2
The sum for the left sides is 2x and the sum for the right sides is 20 + 10 = 30
Setting them equal, we get 2x = 30
Step 3
2x = 30
Solve for x by dividing both sides of this equation by 2
(2/2)x = 30/2
x = 15
Step 4
You can substitute 15 for x in either x + y = 20 or x − y = 10 to get y
Choosing the first one, we get 15 + y = 20
Minus 15 from both sides to get y = 5
Now check yourself that the answer is still the same if you had chosen to substitute 15 for x in x − y = 10
Example #2: Solve the following system using the elimination method
3x + y = 10
4x − 2y = 2
Step 1
First, notice that nothing can be eliminated when adding the left sides since
3x + y + 4x − 2y = 1x + 3y
However, in 3x + y = 10, if I can turn y into 2y, I could elimnate y by adding 2y to 2y in 4x − 2y = 2
Therefore, turn y into 2y by multiplying the whole equation by 2.
2 × ( 3x + y = 10) gives the new equation 6x + 2y = 20
Adding the left side of this equation to the left side of 4x − 2y = 2 gives what you see below:
6x + 2y + 4x − 2y = 6x + 4x + 2y − 2y = 2x + 0 = 2x
Adding the right gives us 20 + 2 = 22
Step 2
The sum for the left sides is 2x and the sum for the right sides is 20 + 2 = 22
Setting them equal, we get 2x = 22
Step 3
2x = 22
Solve for x by dividing both sides of this equation by 2
(2/2)x = 22/2
x = 11
Step 4
You can substitute 11 for x in either 3x + y = 10 or 4x − 2y = 2 to get y
Choosing the first one, we get 3 × 11 + y = 10
33 + y = 10
Minus 33 from both sides to get y = 23
You should have noticed that the reason we call this method the elimination method is because the first thing you do is eliminate a variable

Mar 13, 19 11:50 AM
Learn how to derive the equation of an ellipse when the center of the ellipse is at the origin.
Read More
New math lessons
Your email is safe with us. We will only use it to inform you about new math lessons.